Positive Cooperativity Induced by Interstrand Interactions in Silver(I) Complexes with α, α′‐Diimine Ligands. Issue 42 (30th June 2022) - Zare, Davood; Piguet, Claude; Prescimone, Alessandro; Housecroft, Catherine E.; Constable, Edwin C.
Abstract: Invited for the cover of this issue are Davood Zare, Claude Piguet, Edwin C. Constable and co‐workers at the University of Basel and the University of Geneva. The image depicts a [Ag I L] + intermediate about to catch a second α, α′‐diimine ligand to form the stable [Ag I L2 ] + . Read the full text of the article at 10.1002/chem.202200912 . Abstract : " We did not expect to find significant differences in the intimate details of the coordination events occurring with substituted and unsubstituted ligands ." This and more about the story behind the front cover can be found in the article at 10.1002/chem.202200912 ).